Tourette syndrom - a review of current literature - Justyna Wójcik-Grudzień; Martyna Rozenbajgier; Alicja Ozga-Stachurska; Paulina Pawłowska (Kazimierz Wielki University, 2022)
Introduction Tourette syndrome is a disorder characterized by tics. It usually begins in childhood and often remains in adulthood. Tiki is best described as body movements performed automatically excluding the patient's will. It affects boys more often than girls and is associated with attention deficit hyperactivity disorder and obsessive-compulsive disorder. The etiology of Tourette syndrome has not yet been fully clarified. The aim of the study Review the latest literature on Tourette syndrome. Material and methods The research was conducted using Articles by PubMed and Google Scholar on Tourette syndrome. Description of the state of knowledge Tourette syndrome is a movement disorder most commonly found in schoolchildren. The occurrence peaks in the pre-puberty period, and half of the cases disappear in early adulthood and, while the severity of occurrence is higher than commonly assumed.  It is often associated with mentally concomitant diseases, mainly attention deficit hyperactivity disorder and obsessive-compulsive disorder. Given the diverse presentation, Tourette's syndrome can mimic many hyperkinetic disorders, making it difficult or delaying correct diagnosis.  Treatment can be behavioral, pharmacological or surgical and is dependent on the symptoms causing the greatest dysfunction. Summary       Tourette syndrome can cause severe stress and worsen health-related quality of life. Often it is an embarrassing condition for patients. Treatment is multimodal, however, an important issue of treatment among patients is to undertake psychotherapy, so as not to perpetuate the tic reflex, as well as to cope with functioning in society.